A microanalysis study of EFL teacher self-regulation in COVID-19 emergency remote teaching - Dong Li (Journal of China Computer-Assisted Language Learning)
Teacher self-regulation is under-studied yet important especially for teachers of English as a foreign language (EFL) who need to conduct remote teaching over the internet due to COVID-19, known as emergency remote teaching (ERT). In light of the teacher development and self-regulation model that consists of the three phases of forethought, performance and self-reflection, this qualitative study applies the microanalysis method to explore how one novice-level and two master-level Chinese university EFL teachers self-regulated their ERT teaching. After synthetical term frequency analysis using jiebaR, we summarised a total of 14 teacher self-regulation strategies corresponding to the three phases and categorised them into ERT goals (three strategies), motivation for ERT (three strategies), self-control in ERT (three strategies), self-observation in ERT (one strategy), self-judgment from the ERT class (two strategies) and self-reaction from the ERT class (one strategy). We ended by proposing a tentative EFL teacher self-regulation model for ERT context. Implications are provided.